2020
DOI: 10.1021/acs.chemmater.9b03879
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally Low Activation Energy in Cubic Na3SbS4 Superionic Conductors

Abstract: Inorganic Na-ion superionic conductors play a vital role in all-solid-state Na batteries that operate at room temperature. Sodium thioantimonate (Na3SbS4), a popular sulfide-based solid electrolyte, has attracted serious attention due to its advantages of high ionic conductivity at room temperature and impressive chemical stability under ambient conditions. Much research detailing Na3SbS4 focused on its synthetic approaches and interfacial stability against Na metal, yet, there is limited information elucidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 47 publications
5
45
1
1
Order By: Relevance
“…demonstrates the Arrhenius conductivity plot. The activation energy calculated from the fitting result is E a = 0.23 eV, which is in consistent with the value of tetragonal Na 3 SbS 4 reported previously [46,47]. Therefore, Na 3 SbS 4 prepared via the solution method could be tetragonal.…”
Section: Resultssupporting
confidence: 90%
“…demonstrates the Arrhenius conductivity plot. The activation energy calculated from the fitting result is E a = 0.23 eV, which is in consistent with the value of tetragonal Na 3 SbS 4 reported previously [46,47]. Therefore, Na 3 SbS 4 prepared via the solution method could be tetragonal.…”
Section: Resultssupporting
confidence: 90%
“…Ion doping and substitution are common methods of material modification (Bo et al, 2016;Kato et al, 2016;Richards et al, 2016;Krauskopf et al, 2017;Rao et al, 2017;Wang et al, 2017;Mahmoud et al, 2019;Wan et al, 2020;Zhang et al, 2020). Cation ion doping into the P site or halogen doping into the S site can introduce vacancies to improve the ionic conductivity of the CSEs (Zhang et al, 2015;Bo et al, 2016;Wang et al, 2016;Krauskopf et al, 2017Krauskopf et al, , 2018aYu et al, 2017).…”
Section: Ion Doping and Substitutionmentioning
confidence: 99%
“…Moreover, inorganic solid electrolytes include Na-β-Al 2 O 3 , NASICON (Na super ionic conductor), borohydride, and chalcogenide. At present, chalcogenide solid electrolytes (CSEs) are mainly divided into four categories: Na 3 MS 4 (M = P, Sb) series (Tanibata et al, 2017;Krauskopf et al, 2018a;Noi et al, 2018;Takeuchi et al, 2018;Zhao et al, 2018;Zhang et al, 2020), Na 3 MSe 4 (M = P, Sb) series (Bo et al, 2016;Mahmoud et al, 2019), Na m M x P y X 12 (M = Si, Ge, Sn; X = S, Se; 10 ≤ m ≤ 11; x/y = 1/2 or 2) series (Kato et al, 2016;Richards et al, 2016;Wan et al, 2020), and Na 7 P 3 X 11 (X = O, S, Se) series (Wang et al, 2017). The most common in the Na 3 MS 4 (M = P, Sb) series is Na 3 PS 4 , which has two crystal forms: tetragonal (P −4 21 c; a = b = 0.69520 nm, c = 0.70757 nm) and cubic (I −4 3 m; a = b = c = 0.70699 nm) (Tanibata et al, 2017;Krauskopf et al, 2018a;Takeuchi et al, 2018;Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Progress in Na and K metal anodes and related solid‐state ionic conductors [35–37] provide a potential path for safe sodium metal batteries and possibly potassium metal batteries. SSE and all solid state batteries (ASSBs) based sodium thioantimonate (Na 3 SbS 4 ) and related Na 3 PnS 4 (Pn=P, As, Sb) are attracting interest due to their ambient temperature ionic conductivity [36–65] . The undoped Na 3 SbS 4 has been reported to achieve 0.6 mS/cm in its room temperature (RT) tetragonal phase, [66] with markedly increased conductivity occurring in the elevated temperature phases [53, 67] .…”
Section: Introductionmentioning
confidence: 99%
“…SSE and all solid state batteries (ASSBs) based sodium thioantimonate (Na 3 SbS 4 ) and related Na 3 PnS 4 (Pn=P, As, Sb) are attracting interest due to their ambient temperature ionic conductivity [36–65] . The undoped Na 3 SbS 4 has been reported to achieve 0.6 mS/cm in its room temperature (RT) tetragonal phase, [66] with markedly increased conductivity occurring in the elevated temperature phases [53, 67] . Authors reported that light W‐doping at the Sb sites (Na 2.88 W 0.12 Sb 0.88 S 4 and Na 2.9 W 0.1 Sb 0.9 S 4 ) can stabilize the high temperature cubic structure at ambient temperature, boosting the RT ionic conductivity to 41(±8) mS/cm [36, 37] …”
Section: Introductionmentioning
confidence: 99%